Effects of Argentilactone on the Transcriptional Profile, Cell Wall and Oxidative Stress of Paracoccidioides spp. - Araújo, Felipe Souto (PLoS Negl Trop Dis, 2016)
Paracoccidioides spp., a dimorphic pathogenic fungus, is the etiologic agent of paracoccidioidomycosis (PCM). PCM is an endemic disease that affects at least 10 million people in Latin America, causing severe public health problems. The drugs used against pathogenic fungi have various side effects and limited efficacy; therefore, there is an inevitable and urgent medical need for the development of new antifungal drugs. In the present study, we evaluated the transcriptional profile of Paracoccidioides lutzii exposed to argentilactone, a constituent of the essential oil of Hyptis ovalifolia. A total of 1,058 genes were identified, of which 208 were up-regulated and 850 were down-regulated. Cell rescue, defense and virulence, with a total of 26 genes, was a functional category with a large number of genes induced, including heat shock protein 90 (hsp90), cytochrome c peroxidase (ccp), the hemoglobin ligand RBT5 (rbt5) and superoxide dismutase (sod). Quantitative real-time PCR revealed an increase in the expression level of all of those genes. An enzymatic assay showed a significant increase in SOD activity. The reduced growth of Pbhsp90-aRNA, Pbccp-aRNA, Pbsod-aRNA and Pbrbt5-aRNA isolates in the presence of argentilactone indicates the importance of these genes in the response of Paracoccidioides spp. to argentilactone. The response of the P. lutzii cell wall to argentilactone treatment was also evaluated. The results showed that argentilactone caused a decrease in the levels of polymers in the cell wall. These results suggest that argentilactone is a potential candidate for antifungal therapy.